Trends and outcomes of anterior vitrectomy during cataract surgery: a population-based study of cataract surgery outcomes in Western Australia over 22 years - Clark, Antony; Morlet, Nigel; Ng, Jonathon; Preen, D.; Semmens, James (Wiley-Blackwell, 2009)
Purpose: To describe the change in incidence ofanterior vitrectomy during cataract surgery from 1980–2001 and risk of major sight-threatening complications. Method: We used the WA Data Linkage System, which includes all State hospital and death records, to identify patients who underwent cataract surgery in all public and private hospitals in WA for 1980–2001. All procedures where an anterior vitrectomy was performed during cataract surgery were identified using clinical procedure codes. Potential sight-threatening complications were identified from those patients who underwent eye surgery following their cataract surgery. All cases were validated using the hospital medical record. Results: There were 129,982 cataract surgeries performed with 1,342 (10.3%) involving anterior vitrectomy. The incidence of anterior vitrectomy (5–13 per 1,000 procedures) demonstrated two clear peaks in the early-1980s and early-1990s coinciding with the transition of surgical technique. 152 (11.3%) cataract surgeries involving anterior vitrectomy resulted in a sight-threatening complication. This included 50 (3.7%) retinal detachments, 9 (0.7%) pseudophakic bullous keratopathy, 35 (2.6%) IOL dislocations, 5 (0.4%) wound dehiscence cases, 55 (4.1%) dropped nucleuses and 6 (0.4%) endophthalmitis cases. Conclusion: The peaks in anterior vitrectomy reflects the surgeon’s learning curve during the transition from intracapsular to extracapsular extraction and then to phacoemulsification. As expected, patients with anterior vitrectomy had a significantly higher higher risk of complication.